Analisis Peningkatan Kompetensi Guru melalui Penerapan Pembelajaran Berdiferensiasi - Marfu'ah Nursulis; Mohamad Muspawi (Studia Manageria, 2023)
Raising teacher competency is one of the keystone factors that is crucial to raising the standard of education. Teachers have a crucial role in the educational process because they are the primary resource for developing lesson plans, supervising student progress, and creating a supportive learning environment. The research methodology used in this study is a qualitative approach derived from postpositivist theory. This method is typically used to simulate an alamiah situation in which the researcher acts as the primary instrument to illustrate the situation with an objective based on verified facts. This study was conducted at SMPN 14 Kota Jambi using the Subject Study Guide of SMPN 14 Kota Jambi. The results of this research indicate that the implementation of differentiated learning has a positive impact, particularly in enhancing student happiness and the discovery of new experiences. Despite being recognized as significant, there are challenges in identifying diverse learning needs in each class. Teacher competency, as a result of the synergy of various abilities, encompasses technical, interpersonal, intrapersonal, and professional aspects. The evaluation of differentiated learning implementation involves direct observation and document examination, providing a profound understanding of implementation effectiveness and potential challenges.